1997
DOI: 10.1016/s0895-4356(96)00367-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary sex hormone excretions in premenopausal women and coronary heart disease risk: A nested case-referent study in the DOM-cohort

Abstract: D e p a r t m e n t o f In t e r n a l M e d ic in e , A c a d e m ic H o s p it a l U t r e c h t , D e p a r t m e n t o f Epid e m io l o g y a n d H e a l t h C a r e , U n iv e r sit y o f U t r e c h t , a n d D e p a r t m e n t o f E n d o c r in o l o g y , A c a d e m ic H o s p it a l U t r e c h t , 3508 GA U t r e c h t , T h e N e t h e r l a n d s ABSTRACT» The low incidence of coronary heart disease (CHD) in premenopausal women is partly ascribed to protection by endogenous estrogen production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…Other previous studies examining CVD in pre-menopausal women suggest collectively that disruptions in ovarian function are related to an increase in cardiovascular risk; however, such disruptions have been marked by indicators such as anovulation, lower estradiol, and menstrual cycle irregularity and have not included assessments of ovarian reserve in particular. [49][50][51][52][53][54][55] In the current study, the proportion of White women was significantly lower in the low (23%) compared to high (36%) AMH tertile and the proportion of Latina women was significantly greater in the low (29%) compared to mid (22%) and high (19%) AMH tertiles, suggesting there may be a relation between race/ethnicity and AMH. Although most previous studies have included samples comprised of predominately White women, one study comparing AMH declines across race/ethnic groups reported that the average decline in AMH was greater among African-American and Latina women than in White women.…”
supporting
confidence: 39%
“…Other previous studies examining CVD in pre-menopausal women suggest collectively that disruptions in ovarian function are related to an increase in cardiovascular risk; however, such disruptions have been marked by indicators such as anovulation, lower estradiol, and menstrual cycle irregularity and have not included assessments of ovarian reserve in particular. [49][50][51][52][53][54][55] In the current study, the proportion of White women was significantly lower in the low (23%) compared to high (36%) AMH tertile and the proportion of Latina women was significantly greater in the low (29%) compared to mid (22%) and high (19%) AMH tertiles, suggesting there may be a relation between race/ethnicity and AMH. Although most previous studies have included samples comprised of predominately White women, one study comparing AMH declines across race/ethnic groups reported that the average decline in AMH was greater among African-American and Latina women than in White women.…”
supporting
confidence: 39%
“…First-morning voids or overnight collections can be obtained more easily, but may decrease somewhat the reliability of measurements. Most of the studies published on hormone measurements in overnight urine samples or first morning voids use creatinine measurements to adjust for dilution errors [32,33]. Some papers have questioned whether such creatinine adjustments will actually reduce, or rather increase, measurement errors [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The CVD is very low in premenopausal women and there was no evidence about correlation with increased androgens in circulation or urinary excretion with subsequently developed CVD (Gorgels, v d Graaf et al 1997). Furthermore, prospective researches of postmenopausal populations, circulating androgen levels did not correlate with cardiovascular events (Price, Lee et al 1997).…”
Section: Hyperandrogenismmentioning
confidence: 99%
“…This may also underlie the association between hyperandrogenemia and impaired vascular function and reported in some studies involving PCOS subjects (Wu and von Eckardstein 2003). Nevertheless, even though insulin resistance per se has been associated with endothelial dysfunction and increased cardiovascular risk, there is no stable proof that hyperandrogenemia is a risk factor for cardiovascular disease in women (Gorgels, v d Graaf et al 1997).…”
Section: Introductionmentioning
confidence: 99%